Pembangunan Penuras Kuasa Aktif Sambungan Selari Dalam Mengurangkan Harmonik - Md Razali, Norhasniza (Universiti Sains Malaysia, 2006)
An active power filter uses power electronic to generate harmonic current that will cancel the harmonic currents from a nonlinear load. This project is using the three-phase Voltage Source Inverter (VSI) topology as the active power filter with the Sinusoidal Pulse-Width Modulation technique of high frequency switching to produce current outputs of each phase that will cancel the harmonics produced by the usage of nonlinear loads at the three phase transmission line system. This project is started by studying the involved topology, and then designing and simulating circuits using PSPICE V9.1 software. After that, the practical circuits are developed. Both analog and digital methods are applied to the MOSFET switching circuits design in the filter and also for the overall circuits to make sure that the outputs are within the specifications decided. The objective of the project that is to design an active power filter was achieved in both simulation and practically. While the harmonics decrement only can be proved by simulation. The practical circuit cannot be continued because of the lack of time.